2020
DOI: 10.1515/opag-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation, Callus Induction and Regeneration of Ginger (Zingiber officinaleRosc.)

Abstract: AbstractThe present study describes a protocol for micro-propagation, callus induction, and shoot regeneration of ginger (Zingiber officinale). The rhizomes were surface-sterilized with ethanol (70%) for 45 s, sodium hypochlorite (2.5%) for 10 min, and mercuric chloride (0.1%) for 10 min. Multiple shoots were induced from sprouting bud explants cultured on Murashige and Skoog (MS) medium supplemented with 6-benzyladenine (BA) combined with kinetin (Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Apart from BAP, kinetin [23] and thidiazuron (TDZ) [24] also differently influenced shoot multiplication of different varieties of ginger. In addition, a developed root system is the crucial step in plant vegetative propagation, which ensures a high survival rate of micropropagated plantlets during the acclimatization stage [25]. In vitro root induction of ginger is enhanced by auxins supplementation in the culture medium [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from BAP, kinetin [23] and thidiazuron (TDZ) [24] also differently influenced shoot multiplication of different varieties of ginger. In addition, a developed root system is the crucial step in plant vegetative propagation, which ensures a high survival rate of micropropagated plantlets during the acclimatization stage [25]. In vitro root induction of ginger is enhanced by auxins supplementation in the culture medium [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al (2017) reported that the efficiency of shoot bud formation was relied upon and enhanced by supplementing the medium with BA. Similarly, Miri (2020) reported that the increase in BA concentration boosted the induction of axillary shoots of Zingiber officinale Rosc Furthermore, (Zhang et al, 2020) concluded that stem explant which grows on an MS medium containing 1.0mg L -1 BA without NAA giving high shoot multiplication to Malus sieversii.…”
Section: Shooting Regeneration Stagementioning
confidence: 92%
“…Manokari et al (2016) also reported a reduction in H. sabdariffa shoot length from 26 mm to 11 mm with an increasing concentration (1.50-3 mg L -1 ) of BAP. High concentrations of BAP may cause ethylene production that negatively affects shoot regeneration and elongation by restricting lengthening of internodes (Davies et al, 2017;Miri, 2020). Callus formation (arrow) on all explants varied from 510 mm in diameter.…”
Section: Bap Concentration and The Type Of Explantmentioning
confidence: 99%